RACIONALUMO IR TEISINGUMO SĄJUNGOS PROBLEMA JOHNO RAWLSO „POLITINIAME LIBERALIZME“. - Vasiliauskaitė, Nida (Problems / Problemos, 2012)
The article deals with Rawlsian attempts to offer a theoretical model for universal "political, not metaphysical" order, based on the ideas of rationality and justice specifically defined. My point is to reveal the inner inconsistency in the very notion of political liberalism showing that its fundamental presuppositions -- the distinctions of politics / morals and reasonable / rational -- are flawed. Which means that as a project built on two distinct in kind sources of normativity trying to "make them one" without damaging their logical autonomy, political liberalism is deemed to generate inconsistencies and cannot be saved by any "cosmetic changes".